A Thousand Cuts: Cumulative Lead Exposure Reduces Academic Achievement - Alex Hollingsworth; Mike Huang; Ivan Rudik; Nicholas J. Sanders (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study how ambient lead exposure impacts learning in elementary school by leveraging a natural experiment where a large national automotive racing organization switched from leaded to unleaded fuel. We find increased levels and duration of exposure to lead negatively affect academic performance, shift the entire academic performance distribution, and negatively impact both younger and older children. The average treated student in our setting has an expected income reduction of 5,200 in present value terms. Avoiding said treatment has an effect size similar to improving teacher value added by one-fourth of a standard deviation, reducing class size by 5 students, or increasing school spending per pupil by 750. The marginal impacts of lead are larger in impoverished, non-white counties, and among students with greater duration of exposure, even after controlling for the total quantity of exposure.
Keywords: I14; I21; Q51; Q53; 330; education; air pollution; lead; test scores; children